Hubungan self eficacy dengan kualitas hidup pasien TB paru - Syahputra, Febryan Rifky; Yulianti, Yeni; Kusumah, Rani Indriani (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Pulmonary tuberculosis (TB) is an infectious disease that remains one of the leading causes of death worldwide. This disease affects not only the physical condition of patients but also their psychological and social aspects. The quality of life among pulmonary TB patients is influenced by various factors, including self-efficacy, or an individual’s belief in their ability to manage the disease. Purpose: To determine the relationship between self-efficacy and the quality of life of pulmonary TB patients. Method: This study used a cross-sectional design with a quantitative approach. The study population consisted of all 431 pulmonary TB patients, including 58 currently undergoing treatment. The sample size was 58 respondents, using a total sampling technique. The research instruments included the TB Pulmonary Self-Efficacy Scale (TBSES) and the WHOQOL-BREF. Data analysis was performed using the Chi-Square test. Results: The analysis showed a significant relationship between self-efficacy and the quality of life of pulmonary TB patients (p < 0.001). Conclusion: A higher level of self-efficacy contributes to an improved quality of life among pulmonary TB patients. Interventions aimed at strengthening self-efficacy are essential to enhance treatment success and overall patient well-being.   Keywords: Pulmonary Tuberculosis; Quality Of Life; Self-Efficacy.   Pendahuluan: Tuberkulosis paru (TB paru) merupakan penyakit infeksi menular yang menjadi penyebab utama kematian di dunia. Penyakit ini tidak hanya berdampak pada kondisi fisik, tetapi juga aspek psikologis dan sosial pasien. Kualitas hidup penderita TB paru dipengaruhi oleh berbagai faktor, termasuk self-efficacy atau keyakinan individu dalam mengelola penyakitnya. Tujuan: Untuk engetahui hubungan antara self-efficacy dengan kualitas hidup pasien TB paru. Metode: Penelitian ini menggunakan desain cross sectional dengan pendekatan kuantitatif. Populasi penelitian adalah seluruh pasien TB paru sebanyak 431 orang dan yang sedang menjalani pengobatan sebanyak 58 orang. Besar sampel dalam penelitian ini sesanyak 58 responden menggunakan teknik total sampling. Instrumen penelitian meliputi TB Pulmonary Self-Efficacy Scale (TBSES) dan WHOQOL-BREF. Analisis data dilakukan menggunakan uji Chi-Square. Hasil: Analisis menunjukkan adanya hubungan yang signifikan antara self-efficacy dan kualitas hidup pasien TB paru (p < 0.001). Simpulan: Tingkat self-efficacy yang tinggi berkontribusi terhadap peningkatan kualitas hidup pasien TB paru. Intervensi untuk memperkuat self-efficacy penting dalam meningkatkan keberhasilan pengobatan dan kesejahteraan pasien.   Kata Kunci: Self-Efficacy; Kualitas Hidup; TB Paru.